Management of asthma: a consensus statement. Issue 7 (July 1989) - Warner, J O; Götz, M; Landau, L I; Levison, H; Milner, A D; Pedersen, S; Silverman, M
Abstract : In developing these international guidelines there were several unifying themes in the diagnosis and simple management of childhood asthma. For the purposes of the meeting, asthma was operationally defined as 'episodic wheeze and/or cough in a clinical setting where asthma is likely and other rarer conditions have been excluded'. In making a diagnosis of asthma, a full history is a prerequisite. Additional tests are only used to support clinical impression and to provide objective evidence for therapeutic recommendations. General features of a multidisciplinary approach include an appreciation of the importance of psychosocial factors, counselling, and education. Drugs should be prescribed in a rational sequence: beta 2-stimulants for mild episodic wheeze; sodium cromoglycate for mild to moderate asthma; inhaled steroids for moderate to severe asthma; with xanthines, ipratropium bromide, and oral steroids having their place in more persistent and severe cases. Children and their parents should be reassured that if asthma is properly controlled there is no reason why the child should not lead a normal and physically active life. The management of asthma is rewarding and return to 'normal' lifestyle is nearly always possible with active participation in sporting activities.